Pengelolaan Keuangan, Sistem Informasi Akuntansi dan Transparansi Kinerja Keuangan Pada BUMDes - Sagala, Mustofa Kamal Ahmad; Siregar, Saparuddin (E-Jurnal Akuntansi; Vol 33 No 6 (2023)DO - 10.24843/EJA.2023.v33.i06.p015, 2023)
The aim of this research is to find out how financial management and the use of accounting information systems have an impact on the transparency of the Sei Merah BUMDes financial performance to help improve economic welfare in villages. The cross-sectional method was used in this study using simple random sampling of 149 participants registered at BUMDes Sei Merah, and 40 active respondents were selected as research samples. Analysis was performed using multiple linear regression method. The results of the study prove that financial management variables have a significant effect on the transparency of financial performance and accounting information systems have a significant effect on the transparency of financial performance. Keywords: Financial Performance Transparency; Financial Management; Accounting Information System; BUMDes